The ethical aspects of homosexuality - Cassani, Massimo (Medicina e Morale, 1989)
To question the moral aspect and meaning of a given behavior is to question the degree of freedom contained and expressed in it. And by freedom I mean here not only the possibility of doing what one wishes, but, much more profoundly, of building oneself up, of maturing in accordance with one's being, one's dignity and vocation as a man. That is, true freedom consists in succeeding in self-actualization in accordance with one's own nature, in being more and more and better men.